Too close to me : the middle-aged consequences of revealing a child called "it" - Pelzer, David J. (Rosettabooks, 2015)
"In the blockbuster autobiography A Child Called "It," Dave Pelzer shared the story of his childhood--one of the most dramatic and extreme stories of child abuse ever prosecuted in the state of California. As a child, Pelzer was beaten, starved, and abused both emotionally and physically by his alcoholic and mentally unstable mother. As a man, Pelzer went on to have love, happiness, a fulfilling career, and his own family. To many, Pelzer seemed to have found his happy ending. But for a child abuse survivor, living a normal adult life carries challenges and complications above and beyond those faced by most people. This book, the fifth in Pelzer's nonfiction series, provides an honest and courageous look at the difficulties inherent in marriage, parenthood, work, and life from the perspective of someone who survived horrific physical and emotional terrors as a child--and who seeks to meet the responsibilities and complications of adult life with love, strength, and an open heart." -- Dust jacket.